Fenomena Budaya Desain Minimalis Masyarakat Kota - Badriyah, Siti (Pendhapa, 2009)
Solo (Surakarta) is a cultural city showing a significant progress. Although its transmission process is completely influenced by a cultural border, which is considered by the people as a great matter, the acculturation process that influences a visual culture cannot be ignored. The significant progress can be observed from its physical structure of site plan and other factors. While the city visualization that shows a crowd of business and trade community as well as education reflects its rapid progress. A variety number of cultural products inevitably support the city visualization, which attract its people’s consumptive behavior. The writer is interested in choosing the phenomenon of the presence of minimalist-style housing complex that is like an epidemic in this city, especially in Adisucipto region and other strategic regions.Observation and interview were used as the methods of this study. The techniques used in this study were content analysis and data analysis using a procedure of: an analysis done when the process of data collecting was done (Miles and Hubermen, 1984: 21-25) with some steps: (1) data reduction, (2) data reporting, and (3) verification. Those methods were applied by the writer to discuss the phenomenon of minimalist-style housing complex in Surakarta, which focuses on the things that give a background of the presence of it. It consists an interaction between traditional and modern ambivalence as well as between the maintained aspects and conditioned aspects. The two aspects will be mediated with a given concept that is agreed by the visual culture consumers, so that an unwritten agreement that brings the identity of Solo city itself can be obtained in the future in line with the demand of the era. Keywords : phenomenon, minimalist, epidemic.